Łączą nas wspólne cele. Analiza zasad uspołecznienia procesów programowania strategicznego gmin i powiatów = We are united by common goals. Analyzing the rules of socialisation of strategic programming for communes and municipalities - Frątczak-Müller, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to analyse how efficient the functioning of self-governments is in the sphere of strategic programming. The authors pay particular attention to the rules used for the socialisation of this process and their consequences for social life practice. Strategic planning is essential for coordinating activities of institutions and persons around development goals provided in strategic documents. Planning depends on the strength of the innovation capability of the persons holding executive positions in local self-government units and on the competence of the teams cooperating with them.
Keywords: programowanie strategiczne; działania pozorne; niesprawność funkcjonalna; sfera publiczna; proces uspołecznienia; strategic programming; functional inefficiency; public sphere; socialisation process